Milady's standard comprehensive training for estheticians - Janet D'Angelo (Thomson/Delmar Learning, 2003)
This premier edition of Milady?s Standard System of Salon Skills: Skin Care provides students with coverage of all the basic esthetic skills, but also expands into advanced techniques and the latest products and equipment in the skin care field. Each chapter is written by an industry expert, with step-by-step technicals clearly depicted through photographs and illustrations-many of which are also featured on the 12-tape Video Library. This comprehensive, easy-to-understand resource is suitable for 600 to 1200-hour programs with special emphasis on providing estheticians with the communication, business, and retailing skills essential to their profession. This new system keeps pace with the booming esthetics industry providing the theoretical, practical, and essential information every skin care professoinal needs to succeed